2021
DOI: 10.1590/1413-7054202145010021
|View full text |Cite
|
Sign up to set email alerts
|

Environmental degradation risk by water erosion in a water producer Colombian Andes basin

Abstract: Globally, soil degradation by water erosion has become one of the major environmental problems in tropical regions, especially under the severe environmental conditions of the Andes. This study aims to detail the soil risk to degradation by water erosion in a water producer basin located in the Tropical Colombian Andes (Combeima River basin), applying the RUSLE model, discussing how to minimize the erosion processes under its environmental conditions (steep slope, climatic variability, soil classes and propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
1
1
0
Order By: Relevance
“…This behavior can be attributed to the fact that the R factor decreases as the altitude changes from the mountainous areas to the lowlands. This coincides with that indicated by Guauque et al (2021), who found the lowest values of the R factor in the highest areas of the Combeima basin (Colombian Andes), due to the low amount of rainfall.…”
Section: Erosivity (R Factor)supporting
confidence: 91%
“…This behavior can be attributed to the fact that the R factor decreases as the altitude changes from the mountainous areas to the lowlands. This coincides with that indicated by Guauque et al (2021), who found the lowest values of the R factor in the highest areas of the Combeima basin (Colombian Andes), due to the low amount of rainfall.…”
Section: Erosivity (R Factor)supporting
confidence: 91%
“…For the estimation of soil loss generated by water erosion, several studies around the world evaluated the negative effects of erosive phenomena [9][10][11][12]. Methods such as the famous Universal Soil Loss Equation (USLE) proposed by [13], a pioneer model to predict soil erosion, were applied [14,15].…”
Section: Introductionmentioning
confidence: 99%